2018
DOI: 10.1111/nhs.12571
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative exploration of fear of childbirth and preferences for mode of birth among Japanese primiparas

Abstract: Antenatal fear of childbirth (FOC) is associated with negative effects, such as postnatal traumatic symptoms. As the birth-related culture of East Asian countries differs from that in Western countries, the aim of the present qualitative, descriptive study was to explore FOC, perceptions for Caesarean section (CS), and obstetric analgesia (OA) among Japanese primiparas. The qualitative, descriptive study included focus group interviews with 11 primiparous women, which were conducted in a birth house and a mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…Other studies have shown that women who give birth by CS following maternal request, more often suffer from psychiatric illness both before and after the CS (Möller et al, 2017;Olieman et al, 2017). In an interview study with Japanese pregnant nulliparous women (Takegata et al, 2018), all participants denied preferring CS delivery due to the fear. They were worried about postoperative pain who could have a negative influence on them; not being able to take care for the baby.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies have shown that women who give birth by CS following maternal request, more often suffer from psychiatric illness both before and after the CS (Möller et al, 2017;Olieman et al, 2017). In an interview study with Japanese pregnant nulliparous women (Takegata et al, 2018), all participants denied preferring CS delivery due to the fear. They were worried about postoperative pain who could have a negative influence on them; not being able to take care for the baby.…”
Section: Discussionmentioning
confidence: 95%
“…They were worried about postoperative pain who could have a negative influence on them; not being able to take care for the baby. Motherhood is very important among Japanese mothers, so even if they have fear of childbirth and were terrified about the birth, it was more important to be a good mother to take care of the baby after birth, than to have a good experience of labour (Takegata et al, 2018). Also, Israeli women were concerned about negative outcomes for their baby, fearing their baby might be harmed during birth and they preferred more epidural use than CS.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand more about determinants for the increased CS rate in Vietnam, a qualitative exploration is necessary as a first step for planning a large-sized quantitative survey in the near future. Specifically, the birth culture of Vietnam, including the perception of the mode of delivery among women [15,16] and a woman's autonomy [17,18] may be different from other countries. In China and Taiwan, CS has been regarded as a safe option among some of the Chinese mothers, who also use traditional Chinese astrology to decide whether CS; this could be one of the reasons for the rise of the CS rate [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…That is, to share the intentions expressed by women and discuss how to achieve them, practitioners in our study gave timely advice to women when they brought upon topics that were relevant; such advices were meant to enable women to create a better self-image regarding their possible participations in family or community, and to promote women's understanding of and expectations toward the options available to them. In this regard, Takegata et al (2018) and Giurgescu, Penckofer, Maurer, and Bryant (2006)…”
Section: Discussionmentioning
confidence: 99%